Characterization of Activin/BMP2 Chimera, AB204, Formulated for Preclinical Studies - Ahn, Chihoon; Maslennikov, Innokentiy; Youn Choi, Jung; Oh, Hyosun; Cheong, Chaejoon; Choe, Senyon (Protein and Peptide Letters, 2014)
AB204 is an Activin/BMP2 chimera, which has been found to exhibit a higher activity than Bone Morphogenetic Protein 2 (BMP2) in osteogenic activity. To prepare AB204 for its preclinical studies, AB204 has been characterized in various formulation buffers. We observed that AB204 purified by ion-exchange chromatography has low water solubility (2.0 mg/ml), whereas it has high water solubility (higher than 10.0 mg/ml) when purified by reverse-phase chromatography. Analysis of the purification procedures reveals that the buffer composition at the lyophilization step determines the solubility. Lyophilization from sodium acetate buffer at pH 4.5 resulted in formation of sodium hydroxide, which caused low solubility of AB204 by pH increase upon reconstitution in water. However, lyophilization from buffers, containing acetic acid or trifluoroacetic acid (TFA) rendered AB204 to be highly soluble. During the course of these analyses, we found a simple procedure to further reduce residual amount of TFA in the purified AB204.
Keywords: trifluoroacetic acid